The Influence of Motivation and Satisfaction on Event Return in Cycling Tourism Events - Anggraini, Ratih; Lingga, Rimba Zulkarnain; Aliandrina, Dessy Aliandrina (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2025)
Sport tourism has rapidly developed as a global phenomenon, making significant contributions to the tourism sector across various countries. In Indonesia, sport tourism shows substantial growth with major sporting events such as the Bali Marathon and Tour de Singkarak attracting both domestic and international tourists. This study aims to explore the role of motivation and satisfaction in driving repeat participation in cycling tourism events in Indonesia. Using a quantitative approach and regression analysis, the results indicate that participant satisfaction has a significant positive impact on repeat participation, with a coefficient value of 0.51, while motivation also has a positive effect but with a smaller coefficient value of 0.191. This research model explains 40.1% of the variability in repeat participation, demonstrating a moderate predictive power. The findings emphasize the importance of prioritizing participant satisfaction and understanding motivational factors to design effective marketing strategies.